NON-AXISYMMETRIC FLOWS ON HOT JUPITERS WITH OBLIQUE MAGNETIC FIELDS - Batygin, Konstantin; Stanley, Sabine (The Astrophysical journal, 2014)
Giant planets that reside in close proximity to their host stars are subject to extreme irradiation, which gives rise to thermal ionization of trace alkali metals in their atmospheres. On objects where the atmospheric electrical conductivity is substantial, the global circulation couples to the background magnetic field, inducing supplementary fields and altering the nature of the flow. To date, a number of authors have considered the influence of a spin-pole aligned dipole magnetic field on the dynamical state of a weakly ionized atmosphere and found that magnetic breaking may lead to significantly slower winds than predicted within a purely hydrodynamical framework. Here, we consider the effect of a tilted dipole magnetic field on the circulation and demonstrate that in addition to regulating wind velocities, an oblique field generates stationary non-axisymmetric structures that adhere to the geometry of the magnetic pole. Using a kinematic perturbative approach, we derive a closed-form solution for the perturbed circulation and show that the fractional distortion of zonal jets scales as the product of the field obliquity and the Elsasser number. The results obtained herein suggest that on planets with oblique magnetic fields, advective shifts of day side hotspots may have substantial latitudinal components. This prediction may be tested observationally using the eclipse mapping technique.